ROLE PLAYING-ASSISTED PBL MODEL TO IMPROVE STUDENT UNDERSTANDING IN GRADE V OF ELEMENTARY SCHOOL - Iip Miftahudin; Devi Afriyuni Yonanda; Dudu Suhandi Saputra; Beti Istanti Suwandayani; Cucun Sutinah (Universitas Majalengka, 2025)
This study aims to examine the effectiveness of the Problem Based Learning (PBL) model combined with the Role Playing method in improving students’ understanding of civic education content in fifth-grade elementary classes. The study was motivated by the low student engagement and learning outcomes in Civic Education (PKn), which is still predominantly delivered through lectures. PBL encourages real-world problem-solving, while Role Playing allows students to experience civic roles firsthand through simulation.A qualitative approach with a case study design was used. The participants were 17 fifth-grade students at SD IT Tazkia Insani. Data were collected through observation, interviews, and documentation. The findings revealed that the integration of PBL and Role Playing created a more engaging, student-centered learning environment. Students became more confident, collaborative, and critical in their thinking. Most importantly, students’ understanding of the topic “Duties and Roles of Mayors and Regents” significantly improved, both conceptually and in practical application.These results indicate that Civic Education is more effective when learning involves active participation and real-life context. The PBL model assisted by Role Playing is recommended as a strategy to enhance elementary students’ comprehension of civic concepts and promote character education.